Lipid profiles of patients presenting with acute myocardial infarction in a South African regional hospital - Sirkar, A.; Sadhabiriss, D.; Brown, S.L. (SA Heart Journal, 2018)
Background: Cardiovascular disease is an important cause of morbidity and mortality in South Africa and hyperlipidaemia is a major contributing modifiable risk factor. Objectives: To describe the lipid profiles of patients with acute myocardial infarction and to compare values with recommended target levels outlined in the South African Dyslipidaemia Guideline Consensus Statement. Methods: We performed a retrospective chart review of patients admitted with a diagnosis of acute myocardial infarction to a regional hospital in Durban, South Africa, between 1 January and 31 December 2016. Patients had a non-fasting lipogram taken within the first 24 hours of admission. Results: We enrolled 126 subjects. The mean age was 57.6 (SD ± 9.4) years. One hundred and ten subjects (87.3%) met criteria for hyperlipidaemia. Previous statin therapy was associated with lower LDL-cholesterol values (3.43mmol/L vs. 4.03mmol/L, p=0.02), but only 9 (11.2%) of the 80 subjects on therapy (88.8%) fell below the levels recommended for their risk category by the South African Dyslipidaemia Guideline Consensus Statement. Overall, 23 subjects (18.3% of the entire study group) demonstrated LDL-C values at presentation that were below the recommended values. Conclusions: A high proportion of subjects presenting with acute myocardial infarction show evidence of suboptimal control of pre-existing hyperlipidaemia.